The Greco-Albanian Relations During the Period 1974-1996: From Irredentism to Political Realism - Peponas, Manolis (HAPSc Policy Briefs Series, 2023)
Greece and Albania are two countries that confronted each other several times during the first decades of the 20th century. The fact that both Albanians and Greeks were living for centuries in the same geographical region (Epirus) caused several disputes and the intervention of the Great Powers. However, after several years of armed or political confrontation (1913-1945), Greece understood the necessity for peaceful coexistence. The effort to re-establishment their relations was not easy because of the power of the nationalistic organizations. This paper aims to describe how political realism prevailed against irredentism.